Curcumin Inhibits Gastric Inflammation Induced by Helicobacter Pylori Infection in a Mouse Model - Santos, António M. (2017)
This project was funded by PTDC/SAU-OSM/66323/2006 and SFRH/BPD/34094/2006 research grants from the Fundacao para a Ciencia e a Tecnologia (FCT), Portugal.